Climatic niche limits and community‐level vulnerability of obligate symbioses. (1st October 2019) - Smith, Robert J.; Jovan, Sarah; McCune, Bruce
Abstract: Aim: Communities with many species at their climatic niche limits may be vulnerable to species losses, suggesting that niche‐based measures can inform vulnerability assessments. We aimed to quantify spatial variation in community‐level vulnerability indices based on niche limits, not just central tendencies, to predict where climate changes will produce rapid, pronounced shifts in ecological communities. Location: North America. Taxon: Epiphytic lichenized fungi. Methods: We integrated broad‐extent herbarium data (46, 343 North American sites, for estimation of realized niches) with systematic, whole‐community macrolichen surveys from the U.S. Forest Inventory and Analysis inventory (6, 474 U.S. sites, for standardized vulnerability estimation). We introduce three niche‐based vulnerability indices describing (a) percentage of vulnerable species occurring at their upper climatic limits, (b) community‐mean percentile, and (c) deviation of local conditions from community‐mean upper limits. We also performed sensitivity analyses and evaluated vulnerability in future climate change scenarios. Results: Sensitivity of indices to uncertainty in climate variables was minor. Present‐day vulnerability was greatest in north‐central California, in the Southwest along the western Colorado Plateau, and on the Southeastern coastal plain—locations where climatically‐induced compositional changes will become most evident. Under future warming scenarios (+0.5 to + 3.6°C increases), the percentage of U.S. epiphytic macrolichen communities exceeding critical values grew from about 2%–20%. Main conclusions: In all scenarios the most vulnerable communities were concentrated in low‐elevation and southerly locations, suggesting that many ostensibly "warm‐adapted" communities may be close to exceeding their climatic limits. Findings indicate that warming and moisture changes will modify community compositions through the local loss of intolerant species pushed beyond their niche limits. Assessing vulnerability of bioindicators such as lichens will help prioritize locations where the greatest climate‐induced changes in species distributions and diversity will occur.